The effect of free diabetes care on metabolic control and on health-related quality of life among youths with type 1 diabetes in Cameroon - Lontchi-Yimagou, Eric (BMJ Open Diabetes Res Care, 2017)
OBJECTIVE: To assess the effect of free diabetes care on metabolic control and on health-related quality of life (HRQoL) of youths living with type 1 diabetes in Cameroon. RESEARCH DESIGN AND METHODS: We conducted a clinical audit of a multicenter prospective cohort, performed in three of the nine clinics of the ‘Changing Diabetes in Children’ (CDiC) project in Cameroon. We collected data on demography, glycemic control, diabetes acute complications, and patients’ HRQoL at baseline and after 1 year of follow-up. RESULTS: One hundred and four patients (51 female) were included. The mean age was 16±2 years (min–max: 9–18), the mean duration of diabetes was 5±3 years, and the mean HbA1C level was 11.4%±2.7%. A significant reduction in HbA1c (11.4%±2.7% vs 8.7±2.4%), episodes of severe hypoglycemia (27/104 vs 15/104), and episodes of ketoacidosis (31/104 vs 7/104) were observed after 1 year (p<0.05). We did not observe any significant difference in the total HRQoL score (p=0.66). However, we observed a significant decrease in diabetes-associated symptoms (p<0.05). Age, level of education, duration of diabetes, glycemic control, and the presence or absence of diabetes complications did not significantly affect the total HRQoL score. CONCLUSIONS: One year after free diabetes care offered through the CDiC project, a significant improvement was observed in glycemic control and acute complications of diabetes, but not in the total score of HRQoL of youths living with type 1 diabetes enrolled in the project.